Relations between sociocultural spaces and the consumption of psychoactive substances by adolescents - Camila Souza de Almeida; Francisco Carlos Félix Lana (Revista Gaúcha de Enfermagem)
ABSTRACT Objective: To understand the relation between space and psychoactive substance use by adolescents. Methods: This is a mixed method study conducted with 9th grade students from an elementary school in Divinópolis, Minas Gerais. In the quantitative phase (n=303), the modules for general information, use of beverages and illegal drugs from the National School Health Survey were applied. The qualitative phase (n=18) was dominant and followed the quantitative. Descriptive and associated factor analyses were performed for the quantitative variables. Concerning the qualitative aspects, speeches were analyzed based on social determination. Results: Not living with parents and having friends that drink were factors associated with a higher probability of drinking by adolescents. The adolescents' sociocultural spaces are related to the use of beverages and their consequences. Conclusion: The adolescents' views regarding the use of psychoactive substances are influenced by the social and geographical space in which they are inserted.